Pengaruh city branding dan electronic word of mouth terhadap kunjungan wisatawan di Kabupaten Banyuwangi - Shohib Muslim; Nur Hidayati; Pardiman Pardiman (Jurnal Ekonomi Modernisasi, 2021)
This study aims to examine the effect of city branding and electronic word of mouth on the decision to visit Banyuwangi based on the tagline sunrise of java. This research was conducted on the millennial generation in Indonesia. This type of research is explanatory research using a quantitative approach. The data used are primary data obtained based on the results of online questionnaire data from 160 respondents. Sampling using purposive sampling technique with the criteria of respondents having visited at least one tourist destination in Banyuwangi and actively using social media. The results showed that city branding and electronic word of mouth had a positive effect on the decision to visit. Electronic word of mouth has the most dominant influence on visiting decisions compared to city branding. Based on the results of the analysis show that this study provides a theoretical contribution to the factors that influence the decision to visit for tourists, namely city branding and electronic word of mouth. This research also makes a practical contribution in developing strategies to improve visiting decisions.